2023
DOI: 10.1021/acsestengg.3c00004
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Seawater Mineralization and the Mass Balances That Demonstrate Carbon Dioxide Removal

Abstract: We present the mass balances associated with carbon dioxide (CO2) removal (CDR) using seawater as both the source of reactants and as the reaction medium via electrolysis following the “Equatic” (formerly known as “SeaChange”) process. This process, extensively detailed in La PlanteE.C. La Plante, E.C. ACS Sustain. Chem. Eng.2021910731089, involves the application of an electric overpotential that splits water to form H+ and OH– ions, producing acidity and alkalinit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Besides traditional chemical methods, Rau et al also proposed electrochemical technologies to capture CO 2 previously. In their proof of concept, CaCO 3 was utilized to react with the OH – anions generated from water electrolysis to produce Ca­(HCO 3 ) 2 and Ca­(OH) 2 in the cathode part, which would capture CO 2 from the atmosphere to reform CaCO 3 . La Plante et al proposed a single-step carbon sequestration and storage approach that relies on combining dissolved CO 2 in water bodies with Ca and Mg species in an aqueous medium using electrolytic flow reactors and described the mass balances associated with CO 2 removal using seawater as both the source of reactants and the reaction medium by geochemical simulations. , Oloye et al also demonstrated direct air capture of CO 2 using electrochemical approaches, where the efficiency could be increased by the addition of monoethanolamine because CO 2 solubility increased in water . Here, instead of using capture agents, the atmosphere was injected directly into the electrolyzer, where OH – generation by ORR and CO 2 capture occurred simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Besides traditional chemical methods, Rau et al also proposed electrochemical technologies to capture CO 2 previously. In their proof of concept, CaCO 3 was utilized to react with the OH – anions generated from water electrolysis to produce Ca­(HCO 3 ) 2 and Ca­(OH) 2 in the cathode part, which would capture CO 2 from the atmosphere to reform CaCO 3 . La Plante et al proposed a single-step carbon sequestration and storage approach that relies on combining dissolved CO 2 in water bodies with Ca and Mg species in an aqueous medium using electrolytic flow reactors and described the mass balances associated with CO 2 removal using seawater as both the source of reactants and the reaction medium by geochemical simulations. , Oloye et al also demonstrated direct air capture of CO 2 using electrochemical approaches, where the efficiency could be increased by the addition of monoethanolamine because CO 2 solubility increased in water . Here, instead of using capture agents, the atmosphere was injected directly into the electrolyzer, where OH – generation by ORR and CO 2 capture occurred simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…31-34), where aqueous brine (approximately 26 wt %) and NaOH (approximately 28 wt %) are converted into less concentrated brine (approximately 24 wt %), more concentrated NaOH (approximately 30 wt %), hydrogen gas (H 2 ), and chlorine gas (Cl 2 ) (Kumar et al, 2021). The development of efficient and durable oxygen-selective electrodes is critical to making seawater electrolysis more feasible (La Plante et al, 2023).…”
Section: Electrochemical Production Of Alkalinity For Oaementioning
confidence: 99%
“…The precipitation of CaCO 3(s) reduces alkalinity (resulting either in lower efficiency of CO 2 removal per unit of added alkalinity in the case of OAE or a release of CO 2 in cases where the precipitation occurs in the absence of an alkalinity addition), making this second version relatively inefficient from a CO 2 removal perspective, but this may be pursued if other considerations such as ease of verification outweigh this inefficiency. A third version of this approach relies primarily on the precipitation of Mg(OH) 2 , in addition to the precipitation of some CaCO 3, and prevents release of CO 2 in the process of CaCO 3 precipitation by generating alkalinity at a sufficiently high rate to keep the pH at a constant target value (La Plante et al, 2021Plante et al, , 2023.…”
Section: Electrochemical Production Of Alkalinity For Oaementioning
confidence: 99%
“…Presently, the majority of DAC plants use liquid amines as absorbents for the CO 2 , but mineralization is also a potentially promising technique . Mineralization strategies include saline mineralization, , the conversion of silicate minerals, and the weathering of silicate or oxide minerals. However, there are challenges associated with mineralization strategies, for example, passivation layers inhibiting CO 2 uptake can form on silicate minerals due to the polymerization of silicic acid during dissolution and the formation of silica-rich leached layers. , DAC with alkaline metal oxide minerals, such as CaO and MgO, may be cheaper and more feasible compared to other mineral systems if a mineral looping process is used. In this approach, metal carbonates are calcined to form metal oxides that are typically amorphous and highly reactive.…”
Section: Introductionmentioning
confidence: 99%
“…1 Presently, the majority of DAC plants use liquid amines as absorbents for the CO 2 , 2 but mineralization is also a potentially promising technique. 3 Mineralization strategies include saline mineralization, 4,5 the conversion of silicate minerals, 6 and the weathering of silicate or oxide minerals. 7−11 However, there are challenges associated with mineralization strategies, for example, passivation layers inhibiting CO 2 uptake can form on silicate minerals due to the polymerization of silicic acid during dissolution and the formation of silica-rich leached layers.…”
Section: ■ Introductionmentioning
confidence: 99%